Anti-CRISPR: Phage’s Retaliation Discloses The New Defense Plan : Anti-CRISPR, A New Defensive Mechnaism - Ahmed Khalid, Usama; Kanwal, Samra (PSM Microbiology, 2022)
Battle for survival between viruses and bacteria has been continuing for a long time by constantly defeating one another through their different molecular mechanisms. Bacteria use Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR), as a defense mechanism, which performs its activity via Cas enzyme against phages to destroy their inheritance material, i.e., nucleic acids. However, in contrast, phages develop a new arsenal against bacterial attack, named Anti-CRISPR (Acr), that blocks the CRISPR complex. Using an anti-CRIPR mechanism, phages deceive and defeat bacteria by inhibiting binding of CRISPR complex to its original target. As far as molecular applications are concerned, CRISPR and Anti-CRISPR systems are relating to each other in various ways. From defensive approach to molecular plans, both systems are somehow collaborating in multiple ways. This review article is focusing on presenting the development of new phage’s defense and molecular plans of CRISPR and Acr system in precise form. Discovery of new defense system in viruses is good for them, but lot of research is required to identify how multiple genes are evolved against CRISPR.